The impact of prescribed opioids on CD4 cell count recovery among HIV‐infected patients newly initiating antiretroviral therapy1. Issue 10 (November 2016) - Edelman, EJ; Gordon, KS; Tate, JP; Becker, WC; Bryant, K; Crothers, K; Gaither, JR; Gibert, CL; Gordon, AJ; Marshall, BDL; Rodriguez‐Barradas, MC; Samet, JH; et al.
Abstract : Objectives: Certain prescribed opioids have immunosuppressive properties, yet their impact on clinically relevant outcomes, including antiretroviral therapy (ART) response among HIV‐infected patients, remains understudied. Methods: Using the Veterans Aging Cohort Study data, we conducted a longitudinal analysis of 4358 HIV‐infected patients initiating ART between 2002 and 2010 and then followed them for 24 months. The primary independent variable was prescribed opioid duration, categorized using pharmacy data as none prescribed, short‐term (< 90 days) and long‐term (≥ 90 days). Outcomes included CD4 cell count over time. Analyses adjusted for demographics, comorbid conditions, ART type and year of initiation, and overall disease severity [ascertained with the Veterans Aging Cohort Study (VACS) Index]. Sensitivity analyses examined whether effects varied according to baseline CD4 cell count, achievement of viral load suppression, and opioid properties (i.e. dose and known immunosuppressive properties). Results: Compared to those with none, patients with short‐term opioids had a similar increase in CD4 cell count (mean rise per year: 74 vs . 68 cells/μL; P = 0.11), as did those with long‐term prescribed opioids (mean rise per year: 74 vs . 75 cells/μL; P = 0.98). In sensitivity analysis, compared with no opioids, the effects of short‐term prescribed opioids were statistically significant among those with a baseline CD4 cell count ≥ 500 cells/μL (mean rise per year: 52 cells/μL for no opioids vs . 20 cells/μL for short‐term opioids; P = 0.04); findings were otherwise unchanged. Conclusions: Despite immunosuppressive properties intrinsic to opioids, prescribed opioids appeared to have no effect on CD4 cell counts over 24 months among HIV‐infected patients initiating ART.